18F‐FDG PET/CT imaging of small intestinal metastasis from pulmonary sarcomatoid carcinoma: Brief report and review of the literature. Issue 8 (15th May 2020) - Xie, Xinli; Tu, Ning; Wang, Qi; Cheng, Zhen; Han, Xingmin; Bu, Lihong
Abstract : We herein report two cases of small intestinal metastasis from pulmonary sarcomatoid carcinoma (PSC) detected by 18 F‐fluorodeoxyglucose positron emission tomography/computed tomography ( 18 F‐FDG PET/CT). We reviewed the literature on 18 F‐FDG PET/CT features in gastrointestinal metastasis of PSC patients since 1992, and further analyzed the imaging features. According to the literature review, 23 eligible cases were identified from eight studies, and no cases underwent 18 F‐FDG PET/CT imaging. In this study, clinical and PET/CT imaging data of two patients are reported. In our cases, clinical and the CT images of lung masses were not typical, but the uptake of 18 F‐FDG was remarkably high, with SUVmax exceeding 30. Small intestinal metastases may not be related to obstruction, or even the local intestinal cavity may be dilated. Therefore, in PSC patients with mild or without abdominal symptoms, 18 F‐FDG PET/CT imaging could identify intestinal metastasis at a relatively early stage and may be used to determine the preferred biopsy site, or early intervention by surgery. Key points: 18 F‐FDG PET/CT imaging of small intestinal metastasis of PSC has not been previously reported in the literature and here we report the 18 F‐FDG PET/CT features of two cases. The uptake of 18 F‐FDG was remarkably high in both the primary tumor and metastatic intestinal lesion. 18 F‐FDG PET/CT imaging may therefore be used to determine the preferred biopsy site or early intervention by surgery.